Hubungan Motivasi dan Pengetahuan Tentang Fibroadenoma Mammae dengan Tindakan Pemeriksaan Payudara Sendiri (SADARI) pada Mahasiswi Non Kesehatan di Universitas Islam Sultan Agung - Novita Rizkia Suswanti Putri; Moch Aspihan; Abrori Abrori (Pusat Riset dan Inovasi Nasional, 2025)
Mammary fibroadenoma cases can increase the risk of breast cancer and may recur if not properly prevented. Performing SADARI (Breast Self-Examination) can reduce the risk of breast cancer by detecting tumors and cancer early. SADARI in women for early detection of breast cancer is still very low. Some factors that affect SADARI performance include knowledge, attitude, and motivation. To find out the relationship between motivation and knowledge of Mammary Fibroadenoma with the breast self-examination (SADARI) performed by non-health students of Sultan Agung Islamic University. This study was a quantitative analysis with a cross-sectional approach. 361 non-health students became the sample. Sampling in this study used purposive sampling technique utilizing the Sommers'd correlation test. The results showed a relationship between motivation for mammary fibroadenoma and breast self-examination (SADARI) (p value = 0.00), the strength of the correlation was weak (r = 0.28) and the relationship between knowledge about mammary fibroadenoma and breast self-examination (SADARI) (p value = 0.00), the strength of the correlation was weak (r = 0.28). There is a significant relationship between motivation and knowledge about mammary fibroadenoma with breast self-examination (SADARI) among non-health students (p value <0.05).